Night shift : a novel - Cook, Robin, 1940- (Cook, Robin, 1940-. Jack Stapleton & Laurie Montgomery series, 2022)
"In this exhilarating medical mystery-thriller by Robin Cook, fan favorites Jack and Laurie are lured into the dark underbelly of hospital dangers when an internist is murdered"--